Association between divorce and access to healthcare services among married immigrants: propensity score approaches - Suyeong Bae; James E. Graham; Sanghun Nam; Ickpyo Hong (BMC, 2022)
Abstract Background While divorce is a social determinant of health among married immigrants in Korea, its association with access to healthcare services is unclear. Given the rapid increase in the number of married immigrants in Korea, research is needed to improve minority groups' access to healthcare services. Here, we examined healthcare service utilization among married immigrants. Methods We retrieved 11,778 adults from the 2018 Korea National Multicultural Family Survey. We analyzed whether the sex of divorced immigrants is associated with healthcare access using multivariable logistic regression analysis. Further, we analyzed the association between divorce and access to healthcare services among married immigrants using propensity score matching methods. Results There were 691 (5.8%) divorced immigrants in the data set. The married male immigrants had no association between divorce status and healthcare access (adjusted odds ratio [OR] = 1.05, 95% confidence interval [CI] = 0.55-2.03, p = 0.8620). Divorced immigrants were less likely to receive healthcare services than married immigrants (adjusted OR = 1.42, 95% CI = 1.07-1.88). Conclusion Our findings revealed that divorce increases the risk of limited access to healthcare services among married immigrants. Policymakers and healthcare providers should be aware of these potential disparities in this vulnerable minority population.